Analisis Pertumbuhan Ekonomi dan Ketimpangan Wilayah di Provinsi Banten Tahun 2020-2022 - Zaky, Luthfi; Ramdhana, Surya Dinar; Sabitha, Talitha; Kusumawati, Lia (Jurnal Ekonomi-Qu, 2024)
This study aims to analyze the level of economic growth and regional inequality in Banten Province. The source of data in this study is secondary data, namely Gross Regional Domestic Product (GRDP) data of Banten Regency / City and Province, population data of Banten Regency / City and Province, and per capita income data of Banten Regency / City and Province. The analytical tool to be used is the Williamson index. Based on the results of data processing conducted by researchers, the economic inequality of Banten Province in 2020-2022 was very high with a Williamson index range of 0.62-0.73. This study suggests the Banten Provincial Government to pay attention to the resources owned by each district / city in Banten and improve human resources.